Flight period of some parasitoids and a predator of the olive black scale (Saissetia oleae Olivier) on Corfu island - Macropodi Μ. V. (ENTOMOLOGIA HELLENICA, 1987)
The time of year the adults (flight period) of the parasitoids of S. oleae: Μetaphycus helvolus, Μetaphycus lounsburyi, Scutelista cyanea and Moranila californica and the predator Chilocorus bipustulatus are present, was determined in three areas of Corfu island: Lima, Kontocali and Avliotes. M. helvolus apparently has two flight periods: the first is from April till July and the second from November till December. All the other natural enemies have only one flight period per year. The flight period of M. lounsburyi is from April till August, while S. cyanea flies from August till the end of September or the first days of October, and M. californica adults are present from July till the middle of December. Adults of C. bipustulatus appeared from July till December or the middle of January.